1987
DOI: 10.1116/1.583686
|View full text |Cite
|
Sign up to set email alerts
|

GaAs and AlGaAs crystallographic etching with low-pressure chlorine radicals in an ultrahigh-vacuum system

Abstract: Articles you may be interested inChemical dry etching of GaAs and InP by Cl2 using a new ultrahigh-vacuum dry-etching molecular-beam-epitaxy system Damage and contamination-free GaAs and AlGaAs etching using a novel ultrahigh-vacuum reactive ion beam etching system with etched surface monitoring and cleaning method GaAs and AIGaAs have been crystallographic ally etched with low-pressure chlorine radicals in an electron-cyclotron resonance (ECR) plasma shower with a new reactive-ion-beam etching (RIBE) system f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…So, for deep trenches, the assumption of neutral shadowing seems reasonable. Perhaps Knudsen scattered neutrals do reach the bottom in the form of Cl 2 , but since Cl atoms are the more important etchant [42][43][44][45][46][47] the Knudsen diffusion of Cl 2 appears to have only a minor influence on the etching.…”
Section: A Aspect Ratio Scaling Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, for deep trenches, the assumption of neutral shadowing seems reasonable. Perhaps Knudsen scattered neutrals do reach the bottom in the form of Cl 2 , but since Cl atoms are the more important etchant [42][43][44][45][46][47] the Knudsen diffusion of Cl 2 appears to have only a minor influence on the etching.…”
Section: A Aspect Ratio Scaling Mechanismsmentioning
confidence: 99%
“…The source and surface coverage of Cl is modeled by a single effective neutral etchant flux where the differences in reactivity and angular distribution between Cl, Cl 2 , Cl 2 ϩ , and Cl ϩ with Si 42,44 and GaAs 43,[45][46][47] are implicitly averaged. These assumptions are consistent with molecular and ion beam studies of both Si and GaAs etching.…”
Section: Ion-neutral Synergy Model With Langmuir Adsorption and Nomentioning
confidence: 99%
“…Because of the technological importance of these processes, many studies (only some of which are listed here) have looked at how ion beams and plasmas (32)(33)(34)(35)(36)(37), as well as the individual constituents of plasmas [e.g. ions , atoms (38)(39)(40)(41), radicals (26,(42)(43)(44)(45), hot molecules (46,47), electrons (48)(49)(50)(51)(52)(53)(54)(55), and photons (56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)], act to etch semiconductor substrates.…”
Section: Introductionmentioning
confidence: 99%
“…11,[17][18][19][20] In the temperature range up to ϳ300°C only GaCl 3 , AsCl 3 and As reaction products were observed. 23 This ion assistance also drastically reduces the apparent activation energy for etching, leading to non-Arrhenius behavior. 11 McNevin published a Cl 2 /GaAs data base for ⌬H f 0 and S 0 values for all the potential etch products in this system and also found that GaCl 3 and AsCl 3 should be the main products ͑e.g., enthalpies for the mono-, di-, and trichlorides of Ga were Ϫ14.6, Ϫ54.5, and Ϫ99 kcal/mol, respectively, at 298 K͒.…”
Section: Introductionmentioning
confidence: 99%